URGENSI PENDIDIKAN KARAKTER BAGI BANGSA INDONESIA - AH, RABI’ (Fakultas Agama Islam Universitas Islam Madura, 2019)
Character education that has been echoed in a number of years is truly an Islamic character education that is famous for akhlak education. So character education has been in the past, but the implementation has not been maximized. In the present, promoting character education is a necessity, given that the moral condition of the community or students has deteriorated. If in the past the community or students were known for their other polite attitude.Now, with the advancement of civilization, little by little the morale of the nation's children was increasingly degraded. Technological advances for example brought a very significant impact on the moral decline of the community or students themselves. unprofitable and high attitude of selfishness. The loss of national character and Islamic character is a problem that must be addressed immediately because it promotes character education which is inspired by Islamic character education is a must. In this case, the family environment, school and community must integrate with each other to make education successful. So the purpose of this article is to describe the importance of character education and several theories about character education.Both national character education and Islamic character education.